Performance of wall panels with grouted sleeve connector under shear and bending - Nur Izni, Mohd Khir (2014)
This study discussed on the performances of concrete wall panels with grouted sleeve connector under shear and bending test. A substantial fraction of grouted sleeve connector behaviour has been investigated by several researchers from 90's century. Majority of early researches were specific under direct tensile test on connector only. The results show a few failure modes on grout slippage, sleeve fractured and bar fractured and this is considered as Phase 1 in the development of grouted sleeve connector. In Phase 2, the satisfied and selected grouted sleeve connectors from prevised research in Phase 1 were used in precast concrete wall panel. This study was conducted to develop a sleeve connector, using no spiral and reinforced bars only. Then, the connector tested under shear and bending test to study the connection's performance between the bonding of grout and precast concrete wall and analysed the types of failure mode occurred. The performance of connections was evaluated based on the ultimate loading capacity, displacement, strain, stress and failure mode where the strain will record from the use of LVDT (Linear Variable Differential Transducers). The results show that the wall specimens using no spiral and reinforced bar connectors, Wall A (1 - connector) achieved satisfactory structural performance with the ultimate shear capacity 36 % and 66 % higher than Wall B (2-connector) and control wall. Based on the analysis of result, this concluded that the shear cracking at the grout and surface concrete was because of the bonding is not strong.